Kingdom of Morocco : Financial Sector Assessment Update - World Bank (Washington, DC, 2012)
A joint World Bank and International Monetary Fund team visited Morocco in November 2007 at the request of the authorities to update the analysis and recommendations made in the framework of the Financial Sector Assessment Program (FSAP) in 2002 and to assist the authorities in preparing their medium-term strategy for modernizing financial intermediation in Morocco. This Financial Sector Assessment (FSA) summarizes the following main topics: (i) analysis of the progress made by the Moroccan authorities in implementing the recommendations of the 2002 FSAP; (ii) identification of potential risks in the financial sector that could have macroeconomic repercussions or could hamper the development oft he financial system; (iii) assessment of the stability of the financial system and its capacity to manage the risks resulting from the policy of openness, and the system's resistance to these shocks; (iv) review of the authorities' initiatives to increase the rate of bank penetration and improve access to financial services; and (v) assessment of the degree of compliance with the Basel Committee core principles for Effective Banking Supervision (BCP) and with the core principles of the International Association of Insurance Supervisors (IAIS). This report also discussed with the authorities the main points of the capital market surveillance assessment prepared in 2006 by International Organization of Securities Commission (IOSCO), the evaluation by the Arab Initiative for payments and securities settlement systems in 2007, and the MENAFATF assessment of compliance with the Financial Action Task Force on Money Laundering (FATF's) Anti Money Laundering and Combating the Financing of Terrorist (AML-CFT) recommendations in 2007.